POLYPHENOLOXIDASE FROM ATEMOYA FRUIT (ANNONA CHERIMOLA MILL. ANNONA SQUAMOSA L.) - Chaves, Izabella Rodrigues [UNESP]; Ferreira, Ederlan de Souza [UNESP]; Da Silva, Maraiza Aparecida [UNESP]; Neves, Valdir Augusto [UNESP] (Wiley-Blackwell, 2011)
Polyphenoloxidase (PPO) from atemoya fruit was extracted and partially purified by phase partitioning in Triton X-114 (TX-114), ammonium sulfate precipitation and separation on Sephadex G-100. Polyacrylamide gel electrophoresis of the fraction eluted from Sephadex revealed only one band of enzyme activity with a molecular weight of 82 kDa. The achieved purification was 7.12-fold with a recovery of 3.2%. The optimum pH and temperatures were determined for 4-methylcatechol and catechol, and activation energies (Ea) determined. The Km was 5.52 and 79.3 mmol/L for 4-methylcatechol and catechol, respectively. The enzyme showed no activity with L-dihydroxyphenilalanine, pyrogallol, catechin and P-cresol as substrates. Inhibitory effects of phenolic and non-phenolic compounds were tested and the Ki values and type of inhibition determined. Enzyme showed to be relatively unstable at 5570C and Ea for heat inactivation was determined. NaCl and KCl showed to be protective agents of atemoya PPO against thermal denaturation.